An initial investigation of U.S and Vietnamese cultures in contrast through everyday conversations. M.A Thesis Linguistics: 60 22 15 - Nguyễn, Thị Hoàng My (University of Languages and International Studies, 2017)
Mastering a new language does not only consist of the ability to master its system of forms, linguistic but also the competence to understand the way that language used in certain contexts, compared to the mother tongue. Besides the distinctions of phonolo (...)